A CLINICAL ASSESSMENT OF MINISCREWS AS ANCHORAGE SOURCES IN TERMS OF STABILITY, RATE OF TOOTH MOVEMENT, AND ANCHORAGE LOSS - Mashhour Moumneh; Fayez Saleh; Nahed Attia (European Scientific Journal, ESJ, 2014)
The purpose of this study was to investigate the stability of temporary anchorage devices, rate of bodily canine retraction and anchorage loss using miniscrews as a skeletal anchorage mean. The sample comprised twelve patients (3 males and 9 females, age range 17-28 years) who were scheduled for extraction of upper premolars. After leveling and alignment, a pilot drill was used and titanium miniscrews1.2-1.3 mm in diameter and 8 mm length were inserted into the buccal cortical bone between the maxillary second premolars and first molars on both sides. Immediate loading of miniscrews and immediate canine retraction after extraction was performed. The canines were retracted with nitinol springs extending from the canine brackets to the mini-implant. Force magnitude was initially 75 gf and increased to 150 gf after 3 weeks. Patients were seen at 3-week intervals until retraction was considered complete. Stability, gingival index around miniscrews, and patient comfort were rated. Retraction distance evaluated by measuring distance between cusp tip of maxillary canine to buccal cusp tip of maxillary second premolar. Pre and post- retraction panoramic x-rays were taken to categorize type of canine retraction. Pre and post-retraction cephalometric xrays were superimposed for measuring the amount of anchorage loss. The results revealed a success rate of 87.5% of the miniscrews. 62.5% of miniscrews had healthy gingiva, and 12.5% were acutely inflamed. Bodily retraction of canines occurred only in 61.9% of the cases. Mean anchorage loss was 0.21 mm. The first interval had the lowest mean retraction distance The mean rate of retraction was 0.39 mm per week. In conclusion, the TADs are stable absolute anchorage units that can be used for rapid canine retraction. Close relationship exists between implant loss and soft tissue health.